REGIONAL MEDIA PRODUCTION MANAGEMENT IN THE CONTEXT OF ACTIVE MILITARY CONFRONTATION: UKRAINIAN-RUSSIAN CASE STUDY - Viktor Chuzhykov; Andrii Chuzhykov (Izdevnieciba "Baltija Publishing", 2024)
The article examines important aspects of the regional military confrontation, as well as the role and place of the media in the context of escalating hostilities. The paper examines the factors that influence the development, production and distribution of propaganda media products in the context of the transformation of economic, social and ideological relations in the regional information environment. The study identifies and analyses global trends in the development and management of local media. In addition, the budgetary expenditures of NATO countries and the size of their armed forces are compared with similar indicators of Ukraine, Russia, Israel and other countries that demonstrate different trends in military operations. The publication also assesses the capabilities of member states to diversify information and ideological confrontation, in particular at the border.